Empowering Micro and Small Enterprises through Interest-Free Credit: Lessons from Kredit Kukar Idaman - Aini, Aini; Surahman, Surahman; Prayogi, Erwin; Prapdopo, Prapdopo; Kiswanto, M. (PT. Riset Press International, 2025)
Traditional market traders in developing economies often face significant financial challenges, including limited access to formal credit and dependency on high-interest informal loans. This study evaluates the Kredit Kukar Idaman (KKI) program in Kutai Kartanegara, Indonesia, an initiative providing interest-free loans to empower micro and small enterprises (MSEs). Employing a mixed-methods approach, data were collected through surveys, interviews, and focus group discussions with 81 market traders. Results reveal that KKI substantially enhanced financial stability, with 87% of participants reporting increased working capital and 62% expanding their business operations. However, barriers such as limited awareness, administrative complexities, and inadequate digital skills hinder program accessibility and efficiency. Comparisons with global best practices highlight the need for integrated capacity-building measures, including financial literacy training and digital adoption initiatives. The study concludes that while KKI demonstrates the potential to foster economic resilience and market competitiveness, addressing implementation challenges is critical for its long-term sustainability. This research contributes to the discourse on inclusive credit policies and provides actionable insights for policymakers aiming to optimize similar programs.